2022
DOI: 10.1002/htj.22551
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characteristics of hydrated salt blended with Tio2 for thermal energy storage

Abstract: Development leads to an increment in the demand for energy. Conventional sources of energy are fulfilling our energy demands but they are crossing environmental barriers resulting in adverse climatic change. Renewable source of energy is becoming popular as a solution to the energy crisis. To reduce the gap between energy demand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Capric acid (Non-paraffin, Fatty acid type) [36] Sodium sulfate decahydrate (SSD) salt hydrate (Salt hydrates) [37] Oleic-Myristic acid eutectic PCM [38] Stearic acid (Non-paraffin, Fatty acid type) [39] Na 2 HPO 4 •12H 2 O hydrated salt (Salt hydrates) [40] Methyl palmitate and lauric acid eutectic mixture [41] Palmitic acid (Non-paraffin, Fatty acid type) [42] NaNO 3 /KNO 3 (Salt hydrates) [43] Lauric acid/myristyl alcohol eutectic mixture [44] Hydrogenated palm stearin (Non-paraffin, Ester type) [45] Palmitic acid-stearic acid/CuO nanoparticles [46] Lauryl alcohol (Non-paraffin, alcohol type) [47]…”
Section: Organics Inorganics Eutecticsmentioning
confidence: 99%
“…Capric acid (Non-paraffin, Fatty acid type) [36] Sodium sulfate decahydrate (SSD) salt hydrate (Salt hydrates) [37] Oleic-Myristic acid eutectic PCM [38] Stearic acid (Non-paraffin, Fatty acid type) [39] Na 2 HPO 4 •12H 2 O hydrated salt (Salt hydrates) [40] Methyl palmitate and lauric acid eutectic mixture [41] Palmitic acid (Non-paraffin, Fatty acid type) [42] NaNO 3 /KNO 3 (Salt hydrates) [43] Lauric acid/myristyl alcohol eutectic mixture [44] Hydrogenated palm stearin (Non-paraffin, Ester type) [45] Palmitic acid-stearic acid/CuO nanoparticles [46] Lauryl alcohol (Non-paraffin, alcohol type) [47]…”
Section: Organics Inorganics Eutecticsmentioning
confidence: 99%
“…Most of these studies used organic PCM in their LHTES setups, and few have looked at how hydrated salt PCM behaves during charging and discharging [15]. Researchers found that among three plate-encapsulated PCMs used in air heat exchangers, the salt hydrated TES module had the largest energy absorption capacity and was thus the best option [16]. This research suggests an LHTES system that uses low-temperature hydrated salt to address these problems.…”
Section: Introductionmentioning
confidence: 99%